A threat monitoring system in enterprise networks with smart mobiles. (2016) - Chen, Zhijiang; Ge, Linqiang; Xu, Guobin; Yu, Wei; Erbacher, Robert F.; Cam, Hasan; Ekedebe, Nnanna
With the development of modern mobile operating systems, computing, and communication technologies, smart mobile devices have been widely used to support rich applications and have been integrated into enterprise networks for organisations to improve business operations. When accessing sensitive pieces of personal and business information, the lack of strong security in smart mobile devices has become a serious issue. In this paper, we developed a threat monitoring system to monitor and detect threats in enterprise networks with mobile devices. We implemented both signature and anomaly based schemes to monitor and detect threats. To evaluate the effectiveness of our threat monitoring system, we used real-world samples of benign apps and malware samples to conduct experiments on Android mobile devices. Our experimental data shows that our developed system can accurately and effectively detect malware on the Android platform while incurring low overhead to the system in terms of energy and CPU usage.